2015
DOI: 10.1016/j.placenta.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum HtrA1 is differentially regulated between early-onset and late-onset preeclampsia

Abstract: This is the first report to show a clear increase of HtrA1 in the maternal circulation during normal pregnancy, consistent with HtrA1 being highly expressed in the placenta. Importantly, this study identified that serum HtrA1 was altered differently in early-onset and late-onset PE pregnancies, highlighting the complex regulation of HtrA1 in the different subtypes. The significant increase of serum HtrA1 in early-onset PE suggests that it may be a potential biomarker for the diagnosis of early-onset PE at dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Placental HtrA1 expression is significantly increased in PE, especially in the early-onset PE subtype [9,[31][32][33]. We have further reported that placental HtrA1 protein is secreted into the maternal circulation, and that the circulating levels of HtrA1 are also significantly elevated in early-onset PE compared to gestationaged-matched controls [10].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Placental HtrA1 expression is significantly increased in PE, especially in the early-onset PE subtype [9,[31][32][33]. We have further reported that placental HtrA1 protein is secreted into the maternal circulation, and that the circulating levels of HtrA1 are also significantly elevated in early-onset PE compared to gestationaged-matched controls [10].…”
Section: Introductionsupporting
confidence: 58%
“…HtrA1 is expressed ubiquitously, but the highest level is found in the placenta [2,3]. To date, dysregulation of HtrA1 has been implicated in a number of diseases such as cancer [4,5], arthritis [6], age-related macular degeneration (AMD) [7], neurodegenerative and neuromuscular disorders [8], and pregnancy complication preeclampsia [9,10]. Intriguingly, while HtrA1 is down-regulated in a number of cancers [4,5,11,12], it is up-regulated in AMD [7,13,14] and preeclampsia (PE) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…bone sialoprotein, fibronectin, elastin, fibromodulin, TGF-β1) [1519] proteins. Subsequently, interest in HTRA1’s contribution to human development and disease is wide ranging, encompassing numerous research fields such as cancer [20, 21], reproduction [22, 23], neurology [17, 24], and the musculoskeletal system [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence strongly suggests that the two PE subtypes have vastly different etiologies, and early-onset PE poses a far more significant maternal risk, with a 20-fold higher mortality rate than late-onset PE [16], [17], [18], [19]. The risk of cardiovascular disease is also much higher in women who have had early-onset than late-onset PE [20], [21], [22], suggesting that endothelial injury is more profound in early-onset than late-onset PE.…”
Section: Introductionmentioning
confidence: 99%